Engineering thioesterase as a driving force for novel itaconate production via its degradation scheme - Ryan S. Wang; Siang-Wun Siao; Jessica C. Wang; Patrick Y. Lin; Claire R. Shen (Metabolic Engineering Communications)
Incorporation of irreversible steps in pathway design enhances the overall thermodynamic favorability and often leads to better bioconversion yield given functional enzymes. Using this concept, here we constructed the first non-natural itaconate biosynthesis pathway driven by thioester hydrolysis. Itaconate is a commercially valuable platform chemical with wide applications in the synthetic polymer industry. Production of itaconate has long relied on the decarboxylation of TCA cycle intermediate cis-aconitate as the only biosynthetic route. Inspired by nature's design of itaconate detoxification, here we engineered a novel itaconate producing pathway orthogonal to native metabolism with no requirement of auxotrophic knock-out. The reversed degradation pathway initiates with pyruvate and acetyl-CoA condensation forming (S)-citramalyl-CoA, followed by its dehydration and isomerization into itaconyl-CoA then hydrolysis into itaconate. Phenylacetyl-CoA thioesterase (PaaI) from Escherichia coli was identified via screening to deliver the highest itaconate formation efficiency when coupled to the reversible activity of citramalate lyase and itaconyl-CoA hydratase. The preference of PaaI towards itaconyl-CoA hydrolysis over acetyl-CoA and (S)-citramalyl-CoA also minimized the inevitable precursor loss due to enzyme promiscuity. With acetate recycling, acetyl-CoA conservation, and condition optimization, we achieved a final itaconate titer of 1 g/L using the thioesterase driven pathway, which is a significant improvement compared to the original degradation pathway based on CoA transferase. This study illustrates the significance of thermodynamic favorability as a design principle in pathway engineering.